Analysis of Student Concepts Understanding in Solving Scientific Literacy on the Topic of Momentum and Impulse. (February 2019) - Al Faizah, W A; Suparmi,; Aminah, N S
Abstract: This study aims to analyze students' concepts understanding in solving scientific literacy on the topic of momentum and impulses. The subjects in this study were 124 students from 4 senior high schools in Sragen. The instrument used in this study was 10 questions in the form of an essay test. The results of the analysis show that 70 (56.45%) of students have conceptual understanding in solving scientific literacy competencies as interpreting scientific data on the subtopic of conservation of momentum and collisions, 30 (24.19%) of students have conceptual understanding in solving scientific literacy competencies as scientific design on the subtopic of impulses, and 24 (19.35%) of students have a conceptual understanding in solving scientific literacy competencies as explaining scientific phenomena on the subtopic of momentum. This shows that some students still do not have a conceptual understanding in solving scientific literacy problems on the topic of momentum and impulses